Pengaruh Aromaterapi Lavender Terhadap Penurunan Nyeri Luka Perineum pada Ibu Postpartum - Feny Rahmawati Ali; Desy Purnamasari; Miftahul Hakiki (WOMB Midwifery Journal, 2025)
Postpartum mothers experience various changes that often cause discomfort in the early postpartum period, one of which is perineal wound pain that can be overcome by administering lavender aromatherapy. The purpose of this study was to determine the effect of lavender aromatherapy on perineal wound pain in postpartum mothers. Type of research Pre-experimental with one group pretest posttest design The population of all postpartum mothers with a sample size of 16 people. The study was conducted from May 12 to June 17, 2024 at the Kabat Community Health Center. The sampling technique used consecutive sampling, measuring instrument Numeric Rating Scale (NRS). The results obtained were not normal data, analysis using the Wilcoxon test. The results of the study before being given lavender aromatherapy had a mean value of 3.00, the lowest was 2 and the highest was 4, after being given lavender aromatherapy had a mean value of 1.81, the lowest was 1 and the highest was 3. The results of the analysis obtained a P value = 0.000 <0.005 so there is an effect of lavender aromatherapy on perineal wound pain in postpartum mothers. This significant reduction in pain intensity indicates that lavender aromatherapy is effective as a complementary treatment in reducing perineal wound pain. Keywords: Lavender aromatherapy, Perineal pain, Postpartum,